Methodical investigation of mineral and trace element concentrations in equine feces with special consideration of the sampling location - Staufenbiel, Lydia; Müller, Anja-Elvira; Gehlen, Heidrun (Tierärztliche Praxis. Ausgabe G, Grosstiere/Nutztiere, 2021)
Objective measurements of the mineral supply in horses are rarely performed. As a result, incorrect elements or an improper amount of elements are provided. The analysis of feces could represent a novel method to evaluate the nutritive supply. The prerequisite is a knowledge of methodological factors influencing the mineral concentration in the fecal samples. Within the scope of this investigation, the effects of different kinds of mineral supply and the influence of the sampling location on the concentration of minerals in equine feces samples were analyzed. Additionally, the methodical error of the measurement procedure was estimated. Six minerals and 22 trace elements in 30 fecal samples of 5 warmbloods, 3 haflinger horses and 2 ponies with differing mineral supplementation (none, calculated amount, mineral lick mass for free intake) were investigated. The samples derived from 3 locations (cranial rectum, ampulla recti and dung heaps) were dried and analyzed using ICP-OES and ICP-MS. Besides a descriptive data analysis, the effects of the fixed factors sampling location and mineral supplementation as well as repeatability and the relative error of the method were assessed. The element concentrations were not influenced by the sampling location, while they varied significantly depending on the type of mineral supplementation. The repeatability of analysis was high with an average measure of certainty of 0.949 (0.894-0.978) and an average median relative error of 0.18 (0.01-0.86). The study outlines a methodological framework for the determination of mineral and trace element concentrations in equine feces. The location of fecal sampling did not affect the results, therefore, preference may be given to noninvasive sample collection from a fecal pile. Furthermore, as the types of mineral supplementation result in significantly differing fecal element concentrations, varying concentrations in feces allow for conclusions concerning the amount of mineral intake of the individual horse.